Improving Learning Outcomes Using the Project-Based Learning Model in the Electronic Control Systems Subject - Suci Anidya Ramadhani; Edy Sabara; Supriadi Supriadi (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Traditional teaching methods that don't involve students in solving practical problems can lead to disengagement and a lack of critical thinking skills, which can lower electronic control system learning outcomes at Vocational School 10 Makassar. This study examines how Project-Based Learning (PjBL) improves student learning compared to conventional methods. This study is quantitative and quasi-experimental. 53 students were split into experimental (PjBL model) and control (conventional) groups. Students' activity observation sheets and pretest and posttest 20-question objective examinations were used to collect data. Data analysis included descriptive statistical tests, N-Gain tests, prerequisite tests (normality and homogeneity), and independent sample T-test hypothesis testing. The results showed that the improvement in learning outcomes in the experimental class was significantly higher than in the control class. This conclusion is evidenced by the average posttest score of the experimental class of 14.00, far exceeding the control class of 9.71. The average N-Gain value of the experimental class reached 0.51 (medium category), while the control class was only 0.17 (low category). Based on the hypothesis test, a Sig. (2-tailed) value of 0.001 < 0.05 was obtained, which confirmed the significant positive influence of the use of the PjBL model. This study provides a practical contribution for educators in vocational schools as a reference for effective innovative learning models to improve project-based technical competencies.